1987
DOI: 10.1002/ajmg.1320260221
|View full text |Cite
|
Sign up to set email alerts
|

A case of the Neu‐Laxova syndrome: Prenatal ultrasonographic monitoring in the third trimester and the histopathological findings

Abstract: A diagnosis of the Neu-Laxova syndrome was made by ultrasonography in the third trimester of pregnancy. Initial ultrasonographic examination, at approximately 28 wk gestation, showed intrauterine growth retardation (IUGR), hypoechoic skeletal structures, kyphosis, feeble fetal activity, and restricted limb movement. Subsequent sonograms showed microcephaly with a receding forehead and prominent eyes, generalised edema and flexion deformities of limbs. Late third trimester findings included polyhydramnios, swel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…The lateral ventricles were dilated, especially the posterior horns, presenting a fetal persistence colpocephaly. Usually hippocampal formations are not identified [Scott et al, 1981;Muller et al, 1987;our cases]. In some cases, aplasia of olfactory structures [PoGySilova et al, 1976;Scott et al, 19811 or hypoplasia of olfactory and optic nerves [our cases] and undeveloped roof structure of the third and fourth ventricles, or hypoplasia of the spinal cord [Scott et al, 1981 ; our cases] were observed.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The lateral ventricles were dilated, especially the posterior horns, presenting a fetal persistence colpocephaly. Usually hippocampal formations are not identified [Scott et al, 1981;Muller et al, 1987;our cases]. In some cases, aplasia of olfactory structures [PoGySilova et al, 1976;Scott et al, 19811 or hypoplasia of olfactory and optic nerves [our cases] and undeveloped roof structure of the third and fourth ventricles, or hypoplasia of the spinal cord [Scott et al, 1981 ; our cases] were observed.…”
Section: Discussionmentioning
confidence: 76%
“…In full-term infants, neurons of the cortical plates are immature, hyperchromic, and have a laminated structure. The tendency to row formation of neurons was noted by Scott et al [1981], Fitch et al [1982], Mueller et al [1983], and Muller et al [ 19871. Three to 6 layers can be found in the cerebral mantle [ Fitch et al, 1982;Muller et al, 1987;our cases]. Horizontal lamination in our cases had much in common with the arrangement of fetal hemispheres at the fourth month.…”
Section: Discussionmentioning
confidence: 83%
“…The case was presented as an example for the question of phenotypic variability in Neu-Laxova syndrome [8]. Pulmonary hypoplasia, and hyperechoic calvaria, associated with acoustic shadowing which obscures any intracranial abnormality was reported in Neu-Laxova syndrome [9,10]. Other CNS abnormalities include lissencephaly, microgyria, hypoplastic cerebellum, abnormalities of corpus callosum and lateral ventricles and aplasia of olfactory structures and the optic nerves.…”
Section: Case Presentationmentioning
confidence: 99%
“…Radioulnar synostosis can also be observed in triploidy [11], but in this case the chromosomal anomaly is diagnostic; this form of synostosis was also reported in two cases of short-limbed craniosynostotic campomelic dysplasia [6]. Flattening of the orbits, joint contractures, and humeroradial alterations are also present in the Neu-Laxova syndrome and in the Sekel-like syndrome, in which, however, the fundamental sign is neonatal microsomia due to delay in intrauterine growth, with microcephaly and abnormal shortness of the limbs, and in which the associated anomalies relate to systems and regions different from those affected in the Antle~Bixler syndrome [7,12,13].…”
Section: /1mentioning
confidence: 93%